TINJAUAN KONDISI FISIK ATLET FUTSAL KABUPATEN KEPULAUAN MERANTI - Afrizal, Muhammad; Vai, Aref; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to find out an overview of the physical condition of futsak athletes in Meranti Islands Regency. This type of research is descriptive. This research will be carried out at the Selatpajang City Futsal Field, while the time of this research is after a proposal seminar has been carried out and approved by the supervisor and examining lecturer. The sampling technique used all members of the population (the entire population was sampled), namely 12 people. Based on the results of research on the physical condition of Meranti Islands Regency Futsal Athletes, the current endurance/bleep test for Meranti Islands Regency Futsal Athletes is in the good category. The speed possessed by Meranti Islands Regency Futsal Athletes is in the good category. The agility run currently owned by Meranti Islands Regency Futsal Athletes is in the poor category. The leg muscle explosive power possessed by Meranti Islands Regency Futsal Athletes is in the medium category. The eye and foot coordination currently possessed by Meranti Islands Regency Futsal Athletes is in the good category. The sit and reach of Meranti Islands Regency Futsal Athletes is in the good category.Keywords: Overview, Physical Condition, Futsal Athlete